Irrigating with cooler water does not reverse high temperature impact on grain yield and quality in hybrid rice - Shi, Wanju; Zhang, Xinzhen; Yang, Juan; Impa, Somayanda M.; Wang, De; Lai, Yusha; Yang, Zijin; Xu, Hang; Wu, Jinshui; Zhang, Jianhua; Jagadish, Krishna S.V. (Elsevier, 2023)
Rice grain yield and quality are negatively impacted by high temperature stress. Irrigation water temperature significantly affects rice growth and development, thus influencing yield and quality. The role of cooler irrigation water in counteracting high temperature induced damages in rice grain yield and quality are not explored. Hence, in the present study two rice hybrids, Liangyoupeijiu (LYPJ) and IIyou 602 (IIY602) were exposed to heat stress and irrigated with water having different temperatures in a split-split plot experimental design. The stress was imposed starting from heading until maturity under field-based heat tents, over two consecutive years. The maximum day temperature inside the heat tents was set at 38 °C. For the irrigation treatments, two different water sources were used including belowground water with cooler water temperature and pond water with relatively higher water temperature. Daytime mean temperatures in the heat tents were increased by 1.2–2.0 °C across two years, while night-time temperature remained similar at both within and outside the heat tents. Cooler belowground water irrigation did have little effect on air temperature at the canopy level but decreased soil temperature (0.2–1.4 °C) especially under control. Heat stress significantly reduced grain yield (33% to 43%), panicles m−2 (9% to 10%), spikelets m−2 (15% to 22%), grain-filling percentage (13% to 26%) and 1000-grain weight (3% to 5%). Heat stress significantly increased chalkiness and protein content and decreased grain length and amylose content. Grain yield was negatively related to air temperature at the canopy level and soil temperature. Whereas grain quality parameters like chalkiness recorded a significantly positive association with both air and soil temperatures. Irrigating with cooler belowground water reduced the negative effect of heat stress on grain yield by 8.8% in LYPJ, while the same effect was not seen in IIY602, indicating cultivar differences in their response to irrigation water temperature. Our findings reveal that irrigating with cooler belowground water would not significantly mitigate yield loss or improve grain quality under realistic field condition. The outcome of this study adds to the scientific knowledge in understanding the interaction between heat stress and irrigation as a mitigation tool. Irrigation water temperature regulation at the rhizosphere was unable to counteract heat stress damages in rice and hence a more integrated management and genetic options at canopy levels should be explored in the future